(untitled) (Journal of Comparative Social Work, 2021)
Exploring gender and feminization in healthcare professions within welfare institutions is an important issue. This article explores the experiences of male immigrant healthcare assistants with racialized features in Norwegian elderly care. A key narrative theme was how notions such as gender and categories of class reinforce structural power relationships, positioning male immigrants in elderly care as “lacking” and/or vulnerable with respect to self-esteem. In the analysis, participants’ experiences were perceived, contested, and negotiated within the themes of: (a) Gender Identities: Negotiations among male immigrant healthcare assistants, and (b) The interwoven process of gender and class. Participatory parity (Fraser, 2008) and perspectives of intersectionality (Crenshaw, 1989) were applied to explore how notions of gender and categories of class limit and reinforce power relationships. The analysis sheds light on how such notions and categories reinforce structural power relationships. Furthermore, the article argues that understanding the impact of gender on the Norwegian care sector must address how specific categories of individuals are affected, in addition to the attendant labour market challenges.